(untitled) (Swiss Medical Weekly, 2013)
The long QT syndrome (LQTS) is a leading cause of sudden death in the young. It is not as rare as previously assumed, given its established prevalence of 1:2,000 live births. It is characterised by prolongation of the QT interval and by the occurrence of syncope, due to torsades-des-pointes ventricular tachycardia, cardiac arrest and sudden death; these life-threatening cardiac events are usually, but not always, associated with physical or emotional stress. It is a genetic disorder, and knowledge of the genotype impacts significantly on management. Extremely effective therapies are available, which makes the existence of undiagnosed affected and symptomatic patients inexcusable. Indeed, mortality for properly treated patients has now declined to around 1% over a 10-year period. This review, aimed at the clinical cardiologist, discusses briefly the essential genetic information and focuses primarily on the main issues of diagnosis and therapy. One special point of interest is in the impact of genetics on clinical management and the potential medicolegal consequences of not pursuing genetic screening in the proband and hence in the family members.